Posicionamiento de maestros y maestras en formación inicial ante un problema socio-científico ambiental planteado a través de un juego de rol. - Valencia-Ruíz, Juliána (Octaedro, 2023)
The development of critical thinking is a key skill that all responsible citizens should cultivate, and it is also essential for fostering scientific competence. Although educational legislation promotes the importance of critical thinking at all stages of education, it is uncommon for teachers to dedicate time to these activities. Among the skills necessary to acquire solid critical thinking is decision making, and role-playing games emerge as suitable tools to promote it while addressing socio-scientific problems in the classroom. In response to the current biodiversity loss crisis, and considering that role-playing games lend themselves well to addressing environmental issues, a role-playing game on this theme was conducted in the locality, involving pre-service primary education teachers from the University of Malaga. The objective was to study changes in decision-making before and after the game, as well as to understand the dimensions involved in the issue. The results revealed that students experienced significant shifts in their positions after the activity, mainly motivated by environmental considerations. Additionally, most changes in stance occurred in relation to the role they had assumed during the game, and the number of dimensions they believed were involved in the issue increased significantly after the experience. These findings underscore the importance of addressing all aspects of a socio-scientific issue in order to take an informed stance, and suggest the inclusion of similar activities in teacher education programs.
Keywords: Investigación activa en educación; Profesores - Formación profesional; Toma de decisiones; Juego de rol; Profesorado en formación inicial